Penerapan augmented reality sebagai media digital marketing di masa Pandemi Covid 19 pada pengusaha penginapan di Malino - Fadliyani Nawir; Aminuddin Hamdat (Universitas Pendidikan Indonesia (UPI), 2021)
The Covid 19 pandemic has had a major impact on industries in Indonesia, especially the tourism sector. Due to large-scale social restrictions making community activities very limited, lodging in tourist areas is empty of visitors. The purpose of this Community Service activity is to provide education about augmented reality technology that can be adopted for marketing media on social media so that lodging entrepreneurs can provide new value for their consumers during this pandemic. The method used in this Community Service activity is the presentation of the augmented reality application for the interior of the inn, workshops on the use of the application, digital marketing techniques on social media that are directly practiced by the speakers and participants which are ended by discussion and question and answer. The results of this service activity are videos produced from augmented reality technology in accordance with the interior of each inn from the participants.